2012
DOI: 10.1107/s1600536812013451
|View full text |Cite
|
Sign up to set email alerts
|

N-(2,6-Dimethylphenyl)-2,2-diphenylacetamide

Abstract: In the title compound, C22H21NO, the dihedral angle between the phenyl rings is 82.59 (7)°. The dimethyl­benzene ring forms dihedral angles of 52.86 (4) and 49.65 (5)° with the two phenyl rings. In the crystal, mol­ecules are linked by N—H⋯O hydrogen bonds, forming a C(4) chain along the c axis. The crystal also features C—H⋯π inter­actions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…The C2-C1-N1-N2, C1-N1-N2-C7, N1-N2-C7-C8, N2-C7-C8-Cl1, N2-C7-C8-Cl2, Cl1-C8-C7-C9 and C8-C7-C9-C14 torsion angles are À1.1 (2), 178.86 (13), 174.62 14, À176.19 (11), 2.9 (2), 5.1 (2) and 63.4 (2) , respectively. Bond lengths (Allen et al, 1987) and angles are within normal ranges and are comparable to those observed in related structures, viz: (2E)-1-(2-hydroxy-5-methylphenyl)-3-(4-methoxyphenyl)prop-2-en-1-one (Fun et al, 2011a), (2E)-3-(3-benzyloxyphenyl)-1-(2-hydroxy-5-methylphenyl)prop-2en-1-one (Fun et al, 2011b), (2E)-3-[3-(benzyloxy)phenyl]-1-(2-hydroxyphenyl)prop-2-en-1-one (Fun et al, 2011c), (2E)-1-(2,5-dimethoxyphenyl)-3-(3-nitrophenyl)prop-2-en-1-one (Fun et al, 2011d) and (2E)-3-(3-nitrophenyl)-1-[4-(piperidin-1-yl)phenyl]prop-2-en-1-one (Fun et al, 2012).…”
Section: Structural Commentarymentioning
confidence: 99%
“…The C2-C1-N1-N2, C1-N1-N2-C7, N1-N2-C7-C8, N2-C7-C8-Cl1, N2-C7-C8-Cl2, Cl1-C8-C7-C9 and C8-C7-C9-C14 torsion angles are À1.1 (2), 178.86 (13), 174.62 14, À176.19 (11), 2.9 (2), 5.1 (2) and 63.4 (2) , respectively. Bond lengths (Allen et al, 1987) and angles are within normal ranges and are comparable to those observed in related structures, viz: (2E)-1-(2-hydroxy-5-methylphenyl)-3-(4-methoxyphenyl)prop-2-en-1-one (Fun et al, 2011a), (2E)-3-(3-benzyloxyphenyl)-1-(2-hydroxy-5-methylphenyl)prop-2en-1-one (Fun et al, 2011b), (2E)-3-[3-(benzyloxy)phenyl]-1-(2-hydroxyphenyl)prop-2-en-1-one (Fun et al, 2011c), (2E)-1-(2,5-dimethoxyphenyl)-3-(3-nitrophenyl)prop-2-en-1-one (Fun et al, 2011d) and (2E)-3-(3-nitrophenyl)-1-[4-(piperidin-1-yl)phenyl]prop-2-en-1-one (Fun et al, 2012).…”
Section: Structural Commentarymentioning
confidence: 99%